Self-Esteem dan Self-Resilience Dalam Al-Qur’an: Solusi Atas Quarter Life Crisis Pada Manusia - Asif Trisnani; Ana Dwi Marlia; Muhammad Thoriqul Islam (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
The quarter-life crisis is now widely experienced across various groups, characterized by identity crises, decreased self-esteem, social pressure, confusion about life goals, and uncertainty about the future. This condition has a direct impact on weakening self-esteem and self-resilience as the foundation of psychological health. However, existing studies are still dominated by a secular-psychological approach and relatively ignore the perspective of the Quran as a source of psychospiritual strengthening. Therefore, this study seeks to systematically examine the concepts of self-esteem and self-resilience in the Quran as an alternative psychospiritual approach to responding to the quarter-life crisis. The method used in this study is a literature review, with a maudhu'i interpretation approach, namely compiling Quranic verses relevant to the themes of self-esteem and self-resilience. Data were obtained from books, journals, proceedings, magazines, and scientific articles, then analyzed using thematic analysis techniques that include the stages of compare, contrast, and critique. The study results show that the Quran builds self-esteem through affirming human dignity, rejecting social comparison as a measure of self-worth, and encouraging resilience and recovery from grief. These values form a healthy self-evaluation framework and serve as psychological protection against the identity crisis of the quarter-life crisis. Furthermore, Quranic self-resilience is built through the internalization of the values ​​of patience, trust (relief), gratitude, and istiqamah (steadfastness), which are integrated into psychospiritual resilience. These values enable individuals to adapt constructively, manage anxiety, and maintain a sense of meaning amid existential pressures. The Quran emphasizes that human worth is not solely determined by worldly achievements, but by a transcendent, divine dimension.